The Implementation of Pancasila Values, Fair and Civilized Humanitarian Principles in Using Social Media - Silaen, Rahel Nathasya; Najicha, Fatma Ulfatun (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
From time to time, the speed of information delivery continues to grow. The tools for communication have also become more sophisticated over time. With globalization and social media accelerating in people's lives, new challenges arise. In writing this journal, the author will describe Pancasila, the values of the second precept, the current situation of social media and the implementation of the value of the second precept in social media as Indonesian citizens.